2021
DOI: 10.1002/cpt.2412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS‐CoV‐2 Infection (COVID‐19) on Cytochromes P450 Activity Assessed by the Geneva Cocktail

Abstract: Coronavirus disease 2019 , caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is a severe acute respiratory syndrome with an underlying inflammatory state. We have previously demonstrated that acute inflammation modulates cytochromes P450 (CYPs) activity in an isoform-specific manner. We therefore hypothesized that COVID-19 might also impact CYP activity, and thus aimed to evaluate the impact of acute inflammation in the context of SARS-CoV-2 infection on the six main human CYPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 53 publications
2
41
0
1
Order By: Relevance
“…The inflammatory status of COVID-19, as well as the release of inflammatory cytokines such as IL-1, IFN, TNFα, and especially IL-6 are associated with decreased activity of drug-metabolizing enzymes and transporters [84] , [87] . As reported, CYP2C19 was associated with the largest decrease in its activity (75 %) after SARS-CoV-2 infection, which inversely associated with the elevation of IL-6, TNF-α, and CRP levels [86] , [88] , [89] . In a cohort study, CYP2C19 activity decreased by 57 % and was found to be negatively correlated with CRP levels [90] .…”
Section: Melatonin As An Anti-coagulant In Covid-19: Mechanisms Of Ac...supporting
confidence: 63%
See 1 more Smart Citation
“…The inflammatory status of COVID-19, as well as the release of inflammatory cytokines such as IL-1, IFN, TNFα, and especially IL-6 are associated with decreased activity of drug-metabolizing enzymes and transporters [84] , [87] . As reported, CYP2C19 was associated with the largest decrease in its activity (75 %) after SARS-CoV-2 infection, which inversely associated with the elevation of IL-6, TNF-α, and CRP levels [86] , [88] , [89] . In a cohort study, CYP2C19 activity decreased by 57 % and was found to be negatively correlated with CRP levels [90] .…”
Section: Melatonin As An Anti-coagulant In Covid-19: Mechanisms Of Ac...supporting
confidence: 63%
“…The activity of CYP450 is inhibited by inflammation in pre-and post-transcriptional pathways [86] . The inflammatory status of COVID-19, as well as the release of inflammatory cytokines such as IL-1, IFN, TNFα, and especially IL-6 are associated with decreased activity of drug-metabolizing enzymes and transporters [84] , [87] .…”
Section: Melatonin As An Anti-coagulant In Covid-19: Mechanisms Of Ac...mentioning
confidence: 99%
“…Interestingly, the CYP3A‐mediated hydroxylation of midazolam in patients with moderate to severe SARS‐CoV‐2 infections was reduced only to a minor extent (22%) compared to the baseline value (after recovery from the infection). 39 However, the potential effect of elevated serum IL‐6 level on the pharmacokinetics of other CYP3A substrates and on the activity of other CYP enzymes (ie, CYP1A2 and CYP2C19) in SARS‐CoV‐2 infection should be considered. 39 It is worth mentioning that dexamethasone as an anti‐inflammatory corticosteroid drug may downregulate the production of IL‐6, potentially offsetting its CYP suppression activity.…”
Section: Discussionmentioning
confidence: 99%
“… 39 However, the potential effect of elevated serum IL‐6 level on the pharmacokinetics of other CYP3A substrates and on the activity of other CYP enzymes (ie, CYP1A2 and CYP2C19) in SARS‐CoV‐2 infection should be considered. 39 It is worth mentioning that dexamethasone as an anti‐inflammatory corticosteroid drug may downregulate the production of IL‐6, potentially offsetting its CYP suppression activity. A complex semimechanistic turnover model may provide further insights into the dynamic interplay between IL‐6 and dexamethasone on net CYP3A activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a review of several studies indicated that the clozapine/norclozapine ratio is not a good measure of CYPIA2 activity or of clinical response, but the authors also noted none of reviewed studies assessed a single subject longitudinally with regards to the clozapine/norclozapine ratio ( Schoretsanitis et al, 2019 ). A recent Swiss study assessed SARS-CoV-2 infection's impact on hepatic cytochromes and reported a 53% inhibition of CYP1A2, 23% inhibition of CYP3A and 75% inhibition of 2C19 enzyme activity, all major metabolic pathways for clozapine during the infection with normalization upon resolution ( Lenoir et al, 2021 ).…”
mentioning
confidence: 99%